Pengaruh gaya hidup dan sikap konsumen terhadap keputusan pembelian - Firdatul Aini; Rifdatul Maulidiyah; Moh Firdaus Hidayanto (JURNAL MANAJEMEN, 2022)
Lifestyle is one of the important factors to be able to influence a purchasing decision at Cafe Gwalk, so optimizing attitudes and lifestyle developments are important things to pay attention to in order to maintain sustainable business growth in global competition. Purchasing decisions can be influenced by various factors, but the biggest influence comes from attitudes and lifestyles, as evidenced by this study through a questionnaire instrument that involved 70 respondents but who entered the criteria there were only 50 respondents from the total number of visitors who came to Cafe Gwalk at the end of November 2021. The regression model of this study was declared feasible based on the results of the F test, and carried out on the T test and it was concluded that both partially and simultaneously attitudes and lifestyle have a significant effect on purchasing decisions.